Pathogenicity Characterization of Prevalent-Type Streptococcus dysgalactiae subsp. equisimilis Strains - Matsue, Miki; Ogura, Kohei; Sugiyama, Hironori; Miyoshi-Akiyama, Tohru; Takemori-Sakai, Yukiko; Iwata, Yasunori; Wada, Takashi; Okamoto, Shigefumi (Frontiers in Microbiology, 2020)
Streptococcus dysgalactiae subsp. equisimilis (SDSE) is an emerging human pathogen that causes severe invasive streptococcal diseases. Recent reports have shown that SDSE exhibits high pathogenicity with different mechanisms from that of Streptococcus pyogenes, although the two streptococci possess some common virulence factors such as streptolysin, streptokinase, and cell-binding proteins. To date, only a few studies have examined the variety of mechanisms expressing the pathogenicity of SDSE. Among nine SDSE clinical isolates sequenced in this study, we present in vitro and in vivo analyses of KNZ01 and KNZ03, whose emm and multilocus species types (MLSTs) are prevalent in Japan and other countries. For the comparison of pathogenicity, we also utilized the ATCC 12394 strain. The whole-genome analysis showed that KNZ03 and ATCC 12394 are categorized into an identical clonal complex by MLST and are phylogenetically close. However, the three strains exhibited different characteristics for pathogenicity in vitro; ATCC 12394 showed significant cytotoxicity to human keratinocytes and release of streptolysin O (SLO) compared to KNZ01 and KNZ03; KNZ03 exhibited significantly high hemolytic activity, but did not secrete SLO. KNZ01 and KNZ03 adhered to human keratinocytes at a higher rate than ATCC 12394; KNZ03 showed a higher rate of survival after a brief (30 min) incubation with human neutrophils compared to the other two strains; also, KNZ01 grew more rapidly in the presence of human serum. In vivo subcutaneous infection commonly resulted in ulcer formation in the three strains 7 days after infection. KNZ01-infected mice showed significant body weight loss 2 days after infection. Besides, on post-infection day 2, only KNZ01 remained in the cutaneous tissues of mice. Scanning electron microscopy analysis revealed that KNZ01 formed an extracellular structure (biofilm), which was probably composed of cell wall-anchoring proteins, in the presence of glucose and human serum. The extracellular structure of ATCC 12394 was also changed dramatically in response to culture conditions, whereas that of KNZ03 did not. Our study proposed that each SDSE strain possesses different virulence factors characteristics for mediating pathogenicity in humans.